ANALYSIS OF PNEUMOCOCCAL VACCINATION EFFICACY AND SAFETY IN CHILDREN WITH VARIOUS DISABILITIES OF HEALTH - A. G. Gaivoronskaya; L. S. Namazova-Baranova; M. G. Galitskaya; T. A. Grechukha; N. E. Tkachenko; M. I. Ivardava (Union of pediatricians of Russia, 2012)
The results of vaccination tolerability assessment against pneumococcal infection in children with various disabilities of health as well as the results of the follow-up of the vaccinated children are cited. The work was carried out at the Vaccination Department of the Scientific Centre for Children's Health, RAMS. It is shown that vaccination against pneumococcal infection was safe as in healthy and in children with various disabilities of health. In the post-immunization period there were no serious adverse events observed (frequency of the expressed general and local postvaccinal reactions didn't exceed 3%). The health of children one year after vaccination remained stable for the underlying disease (if any). It was proved that there was a significant reduction in acute respiratory infections in a group of sickly children, compared with the previous year.